LA OPORTUNIDAD: UN PROGRAMA RADIAL DE LA OFICINA DE OPORTUNIDADES LABORALES .UNAM - GALIAN, CARLOS E.; PASQUET, DANIELA S.; MARTURET, FLORENCIA; MONTIEL, GISELLA; BERNIO, JULIO C.; ARJOL, MARINA G. D.; LAVERAN, MARINA; RIQUELME, MIGUEL; LIBUTTI, SANDRA (Salão do Conhecimento, 2013)
Resumo